Fundamentals of integrated design for sustainable building - Keeler, Marian; Vaidya, Prasad (Hoboken, New Jersey Wiley, 2016)
"Fundamentals of Integrated Design for Sustainable Building offers an introduction to green building concepts as well as design approaches that reduce and can eventually eliminate the need for fossil fuel use in buildings while also conserving materials, maximizing their efficiency, protecting the indoor air from chemical intrusion, and reducing the introduction of toxic materials into the environment. It represents a necessary road map to the future designers, builders, and planners of a post-carbon world"--Provided by publisher.
Chapter 1. The Integrated Building Design Process -- Chapter 2. A History of The Environmental Movements -- Chapter 3. International Conferences and Treaties -- Chapter 4. The Emergence of Green Building and Green Building Policy -- Chapter 5. Chemicals in The Environment, Buildings, And Humans -- Chapter 6. Fundamentals of Indoor Air Quality -- Chapter 7. Indoor Environmental Quality Issues -- Chapter 8. How Buildings Use Energy -- Chapter 9. Reducing Energy Loads -- Chapter 10. Energy-Efficient Hvac Systems -- Chapter 11. Energy Modeling and Measurement -- Chapter 12. Net Zero Energy and Renewable Energy Systems -- Chapter 13. Climate Change and Resilience -- Chapter 14. How Buildings Use Resources -- Chapter 15. Materials Selection and Product Certification -- Chapter 16. How Built Landscapes and Buildings Contribute to Water Quality and Conservation -- Chapter 17. Sustainable Neighborhoods and Communities -- Chapter 18. Rating Systems and Practice Tools -- Chapter 19. Life-Cycle Assessment -- Chapter 20. Waste Management and The Building Industry
Includes index.
Keywords: Sustainable architecture; Architecture -- Environmental aspects